Mitochondrial proteins as therapeutic targets in diabetic ketoacidosis: evidence from Mendelian randomization analysis - Xie, Ruiqiang; Xie, Hongyan; Gao, Hong; Xie, Chunguang; Yuan, Haipo; Feng, Zhijun (Frontiers in Pharmacology, 2024)
Diabetic ketoacidosis (DKA) is a severe and potentially fatal acute complication in diabetic patients, commonly occurring in type 1 diabetes (T1D) but also seen in type 2 diabetes (T2D) . The pathogenesis of DKA involves complex physiological processes that are not fully understood, especially the role of mitochondria. Mitochondria, known as the powerhouse of cells, plays a crucial role in oxidative phosphorylation and ATP production, which is vital in various metabolic diseases, including diabetes. However, the exact causal relationship between mitochondrial dysfunction and DKA remains unclear. This study employed Mendelian randomization (MR) analysis and proteinprotein interaction (PPI) networks to systematically explore the causal relationships between mitochondrial DNA copy number (mtDNA-CN) and specific mitochondrial proteins with DKA. We used bidirectional MR analysis and genome-wide association study (GWAS) data from openGWAS database to investigate the causal effects of mtDNA-CN and 64 mitochondrial-related proteins on DKA and its subtypes (T1DKA, T2DKA, unspecified-DKA). The study revealed that increased mtDNA-CN significantly reduces the risk of DKA, whereas the effect of DKA on mtDNA-CN was not significant. Mitochondrial-related proteins such as MRPL32, MRPL33, COX5B, DNAJC19, and NDUFB8 showed a negative causal relationship with DKA, indicating their potential protective roles.Conversely, ATP5F1B and COX4I2 have a positive causal relationship with DKA, indicating that excessive ATP production in diabetic patients may be detrimental to health and increase the risk of severe complications such as DKA. The results emphasize the necessity of protecting mitochondrial function in order to reduce the risk of DKA. The study offers novel perspectives on the molecular pathways involved in DKA, emphasizing the critical functions of mt-DNA and distinct proteins.These evidences not only enhance our comprehension of the implications of mitochondrial Mitochondrial Proteins as Therapeutic Targets in DKA dysfunction in diabetes-related complications but also identify potential therapeutic targets for individualized treatment approaches, thereby making a substantial contribution to clinical care and public health initiatives.